New era of optogenetics: from the central to peripheral nervous system. (2nd January 2020) - Xu, Xiang; Mee, Thomas; Jia, Xiaofeng
Abstract: Optogenetics has recently gained recognition as a biological technique to control the activity of cells using light stimulation. Many studies have applied optogenetics to cell lines in the central nervous system because it has the potential to elucidate neural circuits, treat neurological diseases and promote nerve regeneration. There have been fewer studies on the application of optogenetics in the peripheral nervous system. This review introduces the basic principles and approaches of optogenetics and summarizes the physiology and mechanism of opsins and how the technology enables bidirectional control of unique cell lines with superior spatial and temporal accuracy. Further, this review explores and discusses the therapeutic potential for the development of optogenetics and its capacity to revolutionize treatment for refractory epilepsy, depression, pain, and other nervous system disorders, with a focus on neural regeneration, especially in the peripheral nervous system. Additionally, this review synthesizes the latest preclinical research on optogenetic stimulation, including studies on non-human primates, summarizes the challenges, and highlights future perspectives. The potential of optogenetic stimulation to optimize therapy for peripheral nerve injuries (PNIs) is also highlighted. Optogenetic technology has already generated exciting, preliminary evidence, supporting its role in applications to several neurological diseases, including PNIs.